A STUDY ON THE FACTORS AFFECTING JOB SATISFACTION OF IT COMPANY WORKERS (International Conference on Education and Innovation, 2025)
Job satisfaction within the Information Technology (IT) sector is critical to retention, productivity, and overall workplace functioning. This research is aimed at understanding the factors that affect the professional life satisfaction of IT experts with regards to work-life balance, parental assistance, career growth, and the organizational climate. A quantitative research strategy was used which involved surveying IT staff from different organizations through proper structuring of questionnaires. The results indicate that work-life balance is the greatest contributor to job satisfaction followed by managerial support and career advancement in that order. In addition, positive organizational culture helps to improve the well-being of employees. The findings can assist IT firms in formulating policies that promote a conducive work environment, reduce turnover, and enhance performance. Though this study captures significant factors, further research is required to broaden the scope of consideration to include other objective and subjective determinants such as salary, employment security, and the psychosocial dimension of well-being by conducting cross-sectional and longitudinal studies on the job satisfaction of IT specialists.